2017
DOI: 10.1111/cas.13169
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of tumor growth and angiogenesis underlies the enhanced antitumor activity of lenvatinib in combination with everolimus

Abstract: The combination of lenvatinib, a multiple receptor tyrosine kinase inhibitor, plus everolimus, a mammalian target of rapamycin (mTOR) inhibitor, significantly improved clinical outcomes versus everolimus monotherapy in a phase II clinical study of metastatic renal cell carcinoma (RCC). We investigated potential mechanisms underlying the antitumor activity of the combination treatment in preclinical RCC models. Lenvatinib plus everolimus showed greater antitumor activity than either monotherapy in three human R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 35 publications
1
40
0
3
Order By: Relevance
“…Everolimus is an inhibitor of mTOR and has clinical benefit in advanced RCC with prior VEGF‐targeted therapies . A preclinical study suggested that simultaneous inhibition of VEGFR, FGFR and mTOR signaling pathways by lenvatinib and everolimus combination resulted in enhanced antitumor activity . In this study, it was considered that lenvatinib in combination with everolimus enhanced the antitumor activity based on the inhibition of VEGF‐ and FGF‐induced angiogenesis by lenvatinib and everolimus, and the direct antitumor activity of everolimus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Everolimus is an inhibitor of mTOR and has clinical benefit in advanced RCC with prior VEGF‐targeted therapies . A preclinical study suggested that simultaneous inhibition of VEGFR, FGFR and mTOR signaling pathways by lenvatinib and everolimus combination resulted in enhanced antitumor activity . In this study, it was considered that lenvatinib in combination with everolimus enhanced the antitumor activity based on the inhibition of VEGF‐ and FGF‐induced angiogenesis by lenvatinib and everolimus, and the direct antitumor activity of everolimus .…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of results from a randomized phase 3 study, lenvatinib was approved for the treatment of radioiodine‐refractory differentiated thyroid cancer in the USA and European Union, and for the treatment of unresectable thyroid cancer in Japan . Lenvatinib in combination with everolimus, an inhibitor of mTOR, is expected to enhance anti‐angiogenesis and antitumor activity by inhibiting VEGFR, FGFR and mTOR signaling pathways . The randomized phase 2 clinical trial carried out in the USA and Europe showed lenvatinib plus everolimus (18 and 5 mg/day, respectively) significantly prolonged PFS with acceptable and tolerable toxicities relative to that of everolimus (10 mg/day) alone (median 14.6 months vs 5.5 months, hazard ratio 0.40, 95% CI 0.24–0.68) in patients with advanced RCC after one prior VEGF‐targeted therapy .…”
Section: Introductionmentioning
confidence: 99%
“…Lenvatinib mesilate (lenvatinib) is an oral multitargeted tyrosine kinase inhibitor with antitumor and antiangiogenic activities via inhibition of VEGFR 1‐3, fibroblast growth factor receptor (FGFR) 1‐4, PDGFR α, RET and KIT . Preclinical studies have demonstrated that lenvatinib has potent antiangiogenic activity through inhibition of both the VEGF and FGF signaling pathways and shows antitumor activity consistently across diverse solid tumor models such as thyroid cancer, renal cell carcinoma (RCC) and HCC . Lenvatinib is used globally to treat progressive, locally recurrent or metastatic, radioactive iodine‐refractory differentiated thyroid cancer, and is used in Japan to treat unresectable thyroid cancer .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, here we show that VEGF might mediate this paracrine action. In keeping with this idea, the combination of Everolimus with Lenvatinib, a multitargeted tyrosine kinase inhibitor that inhibits VEGFR and FGFR exerted higher antitumor activity than monotherapy in model of human renal cell carcinoma xenotransplantation mice …”
Section: Discussionmentioning
confidence: 95%